A prospective study in the Australian petroleum industry. II. Incidence of cancer. Issue 8 (August 1991) - Christie, D; Robinson, K; Gordon, I; Bisby, J
Abstract : This paper reports incidence of cancer in employees of the Australian petroleum industry from 1981 to 1989. Two surveys by personal interview incorporated more than 15, 000 employees, representing 92% of the eligible population. Subjects were included in the analysis after completing five years of service in the industry. At the time of this report the cohort did not include sufficiently large numbers of women for useful analysis; results presented are restricted to the men. On 31 December 1989, 50, 254 person-years of observation had accumulated in the men with 152 incident cancers reported. The standardised incidence ratio (SIR) analysis showed overall cancer rates close to those of the national population. Whereas deficits were seen in some cancer sites, notably lung cancer (SIR 0.5, 95% confidence internal (95% CI) 0.3-0.9), incidence rates for some other cancer sites suggested increased risk. An excess of observed over expected cases was present in all subcategories of lymphohaematopoietic cancer except Hodgkin's disease (no cases), and was most apparent in myeloid leukaemia (SIR 4.0, 95% CI 1.6-8.2). The other major site with a raised number of cases observed over expected was melanoma (SIR 1.4, 95% CI 0.8-2.1).